Comparative study of lipophilic and hydrophilic antioxidants from in vivo and in vitro grown Coriandrum sativum - Dias, Maria Inês (2011)
Coriander is commonly used for medicinal purposes, food applications, cosmetics and perfumes. Herein, the production of antioxidants in vegetative parts (leaves and stems) of in vivo and in vitro grown samples was compared. In vitro samples were clone A- with notorious purple pigmentation in stems and leaves and clone B- green. Seeds were also studied as they are used to obtain in vivo and in vitro vegetative parts. Lipophilic (tocopherols, carotenoids and chlorophylls) and hydrophilic (sugars, ascorbic acid, phenolics, flavonols and anthocyanins) compounds were quantified. The antioxidant activity was evaluated by radical scavenging activity, reducing power and lipid peroxidation inhibition. The in vivo sample showed the highest antioxidant activity mainly due to its highest levels of hydrophilic compounds. Otherwise, in vitro samples, mainly clone A, gave the highest concentration in lipophilic compounds but a different profile when compared to the in vivo sample. Clones A and B revealed a lack of B-carotene, B- and δ-tocopherols, a decrease in alpha-tocopherol, and an increase in Y-tocopherol and clorophylls in comparison to the in vivo sample. In vitro culture might be useful to explore the plants potentialities for industrial applications, controlling environmental conditions to produce higher amounts of some bioactive products.